Impact of Globalization on Postgraduate Students’ Asynchronous Learning in English Language: Muhammad Javed, Akhtar Ali, Azhar Mahmood (PJDOL, 2023)
Globalization affects students’ asynchronous learning. The term asynchronous is usually used to describe communications in which information can be transmitted intermittently rather than in a steady stream. The current study aimed to identify the impact of globalization on postgraduate students’ asynchronous learning in the English language. The students of postgraduate level from distance education institutions were addressed. In this regard, a sample of 600 students was selected by using convenient sampling technique. In order to achieve the objectives of the study, a self-designed questionnaire was administered. D